How effective quantitative tightening can be with a higher-for-longer pledge? - Mika Kortelainen (Bank of Finland, 2024)
We study the effect of quantitative tightening both without forward guidance and with higher for longer guidance. This is done by simulating quantitative tightening strategies in a dynamic stochastic general equilibrium model estimated with the euro area data. Quantitative tightening is quantified by a bond supply shock that raises the long-term term premium. Initially, we assume that quantitative tightening comes without forward guidance, meaning that central bank does not communicate any information regarding the future path of the policy rate. Subsequently, we consider quantitative tightening with forward guidance which is communicated through a higher for longer pledge. In addition, this higher for longer pledge is assumed to be fully credible. We find that if credible, quantitative tightening implemented with forward guidance in the form a higher for longer pledge can tighten monetary policy, albeit a little.
urn:nbn:fi-fe202402167577
Keywords: E52; 330; monetary policy; quantitative tightening; forward guidance